Anomalies in Dopamine Transporter Expression and Primary Cilium Distribution in the Dorsal Striatum of a Mouse Model of Niemann-Pick C1 Disease - Lucarelli, Micaela; Di Pietro, Chiara; La Sala, Gina; Fiorenza, Maria Teresa; Marazziti, Daniela; Canterini, Sonia (Frontiers in Cellular Neuroscience, 2019)
The Niemann-Pick type C1 (NPC1) is a rare genetic disease characterized by the accumulation of endocytosed cholesterol and other lipids in the endosome/lysosome compartments. In the brain, the accumulation/mislocalization of unesterified cholesterol, gangliosides and sfingolipids is responsible for the appearance of neuropathological hallmarks and progressive neurological decline in patients. The imbalance of unesterified cholesterol and other lipids, including GM2 and GM3 gangliosides, alters a number of signaling mechanisms impacting on the overall homeostasis of neurons. In particular, lipid depletion experiments have shown that lipid rafts regulate the cell surface expression of dopamine transporter and modulate its activity. Dysregulated dopamine transporter’s function results in imbalanced dopamine levels at synapses and severely affects dopamine-induced locomotor responses and dopamine receptor-mediated synaptic signaling. Recent studies begin to correlate dopaminergic stimulation with the length and function of the primary cilium, a non-motile organelle that coordinates numerous signaling pathways. In particular, the absence of dopaminergic D2 receptor stimulation induces the elongation of dorso-striatal neuron’s primary cilia. This study has used a mouse model of the NPC1 disease to correlate cholesterol dyshomeostasis with dorso-striatal anomalies in terms of dopamine transporter expression and primary cilium length and morphology. We found that juvenile Npc1nmf164 mice display a reduction of dorso-striatal dopamine transporter expression, with associated alterations of primary cilium number, length-frequency distribution and tortuosity.